Union Business Leave Practices in Large U.S. Municipalities: An Exploratory Study. (December 2017) - Reilly, Thom; Singla, Akheil
This article examines union business leave (UBL) or official time practices among the 77 largest municipalities in the United States. Specifically, it evaluates UBL practices as articulated in 231 collective bargaining agreements (CBAs) of police, firefighter, and nonsafety public employee unions. Results indicate that UBL is prevalent as 72% of unions receive some kind of UBL, most frequently paid leave financed by the city or through cost-sharing arrangements. Empirical findings suggest these practices are driven by political factors, and that resource constraints or the state or regional-level environment are nonsignificant. The article discusses these results and offers a series of policy recommendations.